2019
DOI: 10.1111/pan.13609
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric ventricular assist devices: Bridge to a new era of perioperative care

Abstract: Summary Pediatric ventricular assist devices (VADs) are evolving as a standard therapy for end stage heart failure in children. Major recent developments include the increased use of continuous flow (CF) devices in children and increased experience with congenital heart disease (CHD) and outpatient management. In the current and future era anesthesiologists will encounter more children presenting for VAD implantation, subsequent procedures and heart transplantation. Successful perioperative management requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Additionally, recent reports highlight the ability of CF devices to generate higher flows at lower filling pressures when compared to pulsatile systems. For these reasons, implementing CF devices may be preferred in single ventricle patients with systemic-pulmonary shunts using EXCOR cannulas in combination with a centrifugal pump [18][19][20] . Surgical strategies combining the use of EXCOR cannulas with centrifugal pumps, such as the CentriMag (Abbott, IL, USA) and PediMag (Abbott, IL, USA) devices, additionally provide the ability to exchange a centrifugal device with an EXCOR device when long term-support is necessary to facilitate maximum rehabilitation.…”
Section: The Failing Pre-glenn Svad: Surgical Considerations and Cannulation Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, recent reports highlight the ability of CF devices to generate higher flows at lower filling pressures when compared to pulsatile systems. For these reasons, implementing CF devices may be preferred in single ventricle patients with systemic-pulmonary shunts using EXCOR cannulas in combination with a centrifugal pump [18][19][20] . Surgical strategies combining the use of EXCOR cannulas with centrifugal pumps, such as the CentriMag (Abbott, IL, USA) and PediMag (Abbott, IL, USA) devices, additionally provide the ability to exchange a centrifugal device with an EXCOR device when long term-support is necessary to facilitate maximum rehabilitation.…”
Section: The Failing Pre-glenn Svad: Surgical Considerations and Cannulation Strategiesmentioning
confidence: 99%
“…which may be amenable to interventional coil embolization postoperatively. With the deconstruction of the cavopulmonary anastomosis during device implantation (i.e., SVC reattached to the right atrium with the addition of a systemic to pulmonary shunt to provide pulmonary blood flow), such significant desaturations are unlikely 20 .…”
Section: The Failing Glenn Svad: Surgical Considerations and Cannulation Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As previous studies have repeatedly shown, VAD outcomes for Profile 1 patients are sub-optimal. 4 This would be even more so the case in the Stage 1 population, which explains the dismal outcomes (i.e., the nature of salvage VAD in extremely fragile patients). In comparison, <25% of Stage 2 patients are Profile 1, which suggests different reasons for the equally poor outcome.…”
mentioning
confidence: 99%